Pengaruh Firm Value Terhadap Financial Distress - Adelia Yemima; Yulius Jogi (Business Accounting Review, 2020)
Financial distress and firm value are closely related to information dissemination. Sooner or later the company must immediately realize that it is important to improve performance in order to radiate a positive image to the market. Research on firm value has been conducted, but not many have conducted research examining the relationship between firm value and financial distress. This study aims to determine the effect of firm value on financial distress as well as profitability and firm size as control variables. The samples used in this study were 86 manufacturing sector companies listed on the Indonesia Stock Exchange from 2015-2019. Data processing in this study used the Gretl 2020a software.The results of this study prove that firm value has a significant negative effect on financial distress, firm size has a positive effect on financial distress, and fails to prove the effect of profitability on financial distress.